Histórias e memórias de práticas educacionais relacionadas às pessoas com autismo em Sergipe (1962-1993) - Andrade, Walna Patrícia de Oliveira (2019)
This research has as its object the history of educational practices directed to people with autism in Sergipe, from 1962 to 1993. The main objective was to understand the educational practices related to people with autism in Sergipe, in the period of time studied. The specific objectives were: to constitute a historical survey on the construction of the autism clinical picture, since the first scientific studies carried out until the use of this diagnosis in Sergipe; identify the educational practices in which the public with this disorder participated; understand the role of the family in the educational process of these people and investigate how the state participated in this process. Methodologically, this is a historical research, from the perspective of Cultural History, seeking theoretical support in Chartier (1988), from the identification of how a social reality can be constructed and thought; of documentary nature and combined with the Thematic Oral History, based on Meihy and the Netherlands (2015), through narratives obtained in interviews. The research uses as source 14 interviews, of which 13 were conducted by the author, and laws, statutes, minutes of meetings and regiments collected in the institutions surveyed, as well as photographs and newspapers. The hypotheses arose from the fact that the actions that took effect on the educational possibility of people with autism came from their relatives and not from a public policy with this purpose; that educational practices were geared to activities of daily living and there was no relation to the formal curriculum worked in mainstream schools. People with possibly autism were found to participate in the same educational practices aimed at people with other types of disabilities; that the search for the possibility of inserting people with autism in the educational system always came from their families and that at the beginning of this process there were few government actions in this direction.